Love in the fourth dimension.[article]. - Berscheid, Ellen
Psychologists'efforts to understand love began in the mid-twentieth century. The fact that they continue apace in the twenty-first century reflects increased awareness of the importance of love to understanding relationship phenomena and acknowledgment that an understanding of love has yet to be achieved. This article (a) describe one source of increased recognition that the present confusions sorrounding love must be trancended if progress is to be made in understanding many relationship phenomena;(b) discusses the failure to explicate the love construct, which constitute the major obstacle to the study of love phenomena; (c) discusses the need for a temporal model of love in relationships; and (d) suggests that it is important to consider the presence or absence of four types of love , each of which appears to be associated with different causal conditions and thus is likely to have a different temporal course as an adult relationship moves through time.
Keywords: Companionate love; Romantic love; Compassionate love; adult attachment; Temporal course; Interpersonal relationships